The Clinical and Economic Impact of Generic Locking Plate Utilization at a Level II Trauma Center. (December 2016) - Mcphillamy, Austin; Gurnea, Taylor P.; Moody, Alastair E.; Kurnik, Christopher G.; Lu, Minggen
Abstract : Objectives: In today's climate of cost containment and fiscal responsibility, generic implant alternatives represent an interesting area of untapped resources. As patents have expired on many commonly used trauma implants, generic alternatives have recently become available from a variety of sources. The purpose of this study was to examine the clinical and economic impact of a cost containment program using high quality, generic orthopaedic locking plates. The implants available for study were anatomically precontoured plates for the clavicle, proximal humerus, distal radius, proximal tibia, distal tibia, and distal fibula. Design: Retrospective review. Setting: Level II Trauma center. Patients: 828 adult patients with operatively managed clavicle, proximal humerus, distal radius, proximal tibia, tibial pilon, and ankle fractures. Intervention: Operative treatment with conventional or generic implants. Results: The 414 patients treated with generic implants were compared with 414 patients treated with conventional implants. There were no significant differences in age, sex, presence of diabetes, smoking history or fracture type between the generic and conventional groups. No difference in operative time, estimated blood loss or intraoperative complication rate was observed. No increase in postoperative infection rate, hardware failure, hardware loosening, malunion, nonunion or need for hardware removal was noted. Overall, our hospital realized a 56% reduction in implant costs, an average savings of 1197 per case, and a total savings of 458, 080 for the study period. Conclusions: Use of generic orthopaedic implants has been successful at our institution, providing equivalent clinical outcomes while significantly reducing implant expenditures. Based on our data, the use of generic implants has the potential to markedly reduce operative costs as long as quality products are used. Level of Evidence: Therapeutic Level III.